Zaznavanje, doživljanje in uporaba javnega odprtega prostora prebivalcev v stanovanjskih soseskah mest - Bratina Jurkovič, Nataša (Urbani izziv, 2014)
In cities, public green open spaces offer residents a potentially better quality of life. The behavioural patterns by which people experience and use these spaces is therefore a valuable source of information for spatial planning. Indeed, studying how these spaces are used has also shown a significant difference between the intentions of planners and users. Only the frequency of visits to these public green spaces ultimately testifies to their appropriate and successful planning. Based on empirical research conducted in a residential area of Ljubljana, this article addresses the significance and methods of obtaining information on the experience and use ofurban open spaces by residents of that neighbourhood. The article identifies factors (that could also be used by planners) that significantly impact satisfaction levels among the intended users of the neighbourhood. The focus group method and socio spatial schema method were used, based on the assumption that a multi method approach provides more accurate and reliable information that is verifiable, and therefore more useful in developing planning policies. According to the research findings, residents perceive their "neighbourhood" to be the area around their home in which they know each other and socialise with neighbours. The factors that trigger a sense of satisfaction with their neighbourhood are well maintained green areas in the vicinity of their home, parks with trees that provide spaces for a variety of activities, tree lined streets, green areas connected into a system, the opportunity to use these areas for recreation and sports, and street furniture for rest or play. The spatial elements that hinder the use of such open spaces are, in particular, busy streets, unprotected pedestrian crossings, large garage areas and car parking.
Keywords: mesta; prostorsko planiranje; spatial planning; stanovanjska naselja; urbanistično planiranje; zelene površine